Effect of coconut water and BA on shoot induction of Musa (ABB group) ‘Namwa Mali-Ong’ cultured in vitro - Dechpala, Pikul; Pithayawutwinit, Thitiporn; Pensuk, Viboon (Maejo Journal of Agricultural Production, 2019)
There are several factors involved in banana tissue culture including plant nutrients, types and concentrations of plant growth regulator. This study aimed to investigate the effect of coconut water and benzyladenine (BA) levels on shoot induction of Musa (AAB group) “Namwa Mali-Ong” under aseptic conditions. Explants of the banana were cultured on Semi-solid Murashige and Skoog (MS) media with the addition of 30 g/l sugar and 8 g/l agar. The pH was adjusted to 5.7. The experimental design was 2x4 factorial design in CRD with 4 replications, factors including percentage of coconut water (0 and 20%) and of BA concentrations (0, 3, 4 and 5 mg/l). Data were collected over a 12 week period. The results showed that coconut water had no effect on shoot induction of the bananas. BA concentrations made a significant difference in the number of shoots induced compared to 0 mg/l BA. Interaction effects were found between coconut water and BA. A combination of 0% coconut water and 4 mg/l BA showed the highest level of shoot induction at 3.5 and 5.0 shoots in week 11 and 12, respectively.